Pro Perl Debugging - Lester, Andy; Foley, Richard (Apress : Imprint: Apress, 2005)
Combining the best features of C, UNIX utilities, and regular expressions, Perl has grown as one of the most powerful and popular scripting languages. The valuable Perl is often used for system administration, text processing and Web programming. It is even being used for more exotic areas, like bioinformatics. Perl is supported by all of the most prominent operating systems, including Windows, Unix, OS/2, Amiga, and others. Pro Perl Debugging steps in to help resolve the dilemma of application testing and debugging-one of the biggest time commitments in a programmers daily routine. What this book will do is rescue you from substandard application testing practices. The book commences with several chapters that overview the debuggers basic features, then covers common debugging scenarios. The concluding portion examines debugger customization, alternative debugging utilities, and debugging best practices.